The Critical Function of microRNAs in Developing Resistance against 5- Fluorouracil in Cancer Cells - Sheikhnia, Farhad; Maghsoudi, Hossein; Majidinia, Maryam (Mini Reviews in Medicinal Chemistry, 2024)
Although there have been significant advancements in cancer treatment, resistance and recurrence in patients make it one of the leading causes of death worldwide. 5-fluorouracil (5-FU), an antimetabolite agent, is widely used in treating a broad range of human malignancies. The cytotoxic effects of 5-FU are mediated by the inhibition of thymidylate synthase (TYMS/TS), resulting in the suppression of essential biosynthetic activity, as well as the misincorporation of its metabolites into RNA and DNA. Despite its huge benefits in cancer therapy, the application of 5-FU in the clinic is restricted due to the occurrence of drug resistance. MicroRNAs (miRNAs) are small, non-coding RNAs that act as negative regulators in many gene expression processes. Research has shown that changes in miRNA play a role in cancer progression and drug resistance. This review examines the role of miRNAs in 5-FU drug resistance in cancers.
Keywords: miRNAs